Benefit Duration and Job Search Effort: Evidence from a Natural Experiment - Andreas Lichter (Institute for the Study of Labor (IZA), 2016)
Findings of prolonged non-employment spells due to more generous unemployment benefits are commonly seen as an indication of reduced job search effort and moral hazard behavior. However, to date, there is hardly any direct evidence of benefit-induced reductions in search effort. This paper exploits quasi-experimental variation in the potential benefit duration in Germany paired with individual-level data on job search behavior to directly investigate this assumed relationship. The results of this study provide substantial support for strategic job search behavior in response to the generosity of the benefit scheme: the extension of the benefit duration caused job search effort to significantly decrease, lowering the number of filed applications and the probability of applying for a job that requires moving. In line with theory, it is shown that the reduction in search effort is accompanied by a significant decrease in the short-run job-finding rate. Instrumental variables estimates further provide causal evidence on the direct relationship between search effort and unemployment duration: a 10 percent increase in the number of filed job applications is found to increase the short-run job-finding probability by 1.3 percentage points.
Keywords: D83; I38; J64; J68; 330; job search; unemployment insurance; natural experiment; Germany